Serum miR-125a-5p and CCL17 Upregulated in Chronic Spontaneous Urticaria and Correlated with Treatment Response - Liming Zhang; Ruiqun Qi; Yang Yang; Xinghua Gao; Hongduo Chen; Ting Xiao (Medical Journals Sweden, 2019)
Chronic spontaneous urticaria (CSU) is a common skin disorder associated with autoimmunity. MicroRNAs (miRNAs) are endogenous noncoding RNA molecules reported to be potential biomarkers for some autoimmune diseases. In this study, we investigated the association of miRNAs with CSU. A quantitative PCR (qPCR)-based array was generated from sera as obtained from 20 active CSU patients and 20 healthy controls. Upregulated or downregulated miRNAs were validated by reverse transcription qPCR in sera from 59 active CSU patients and 58 healthy controls. The expression of miR-125a-5p was significantly upregulated in CSU sera and serum levels of CCL17 were also significantly increased in CSU patients. Serum miR-125a-5p expressions were found to be further upregulated in refractory CSU cases (n = 10). In 12 CSU patients in remission, serum miR-125a-5p expression and CCL17 levels were significantly decreased as compared with that obtained in active phase patients. These results indicated that miR-125a-5p and CCL17 can serve as potential serum biomarkers for CSU.